Tobacco road - Caldwell, Erskine 1903-1987 (Brown Thrasher books, 1995)
A tale of violence and sex among rural poor in the American South, the novel was highly controversial in its time. It is the story of Georgia sharecropper Jeeter Lester and his family, who are trapped by the bleak economic conditions of the Depression as well as by their own limited intelligence and destructive sexuality. Its tragic ending is almost foreordained by the characters' inability to change their lives. Caldwell's skillful use of dialect and his plain style made the book one of the best examples of literary naturalism in contemporary American fiction. The novel was adapted as a successful play in 1933.